Investment Behaviour Towards Build-to-Rent in Australia - Piyush Tiwari; Raghu Dharmapuri Tirumala; Godwin Kavaarpuo; Samuel Swanzy-Impraim; Jyoti Shukla (Buildings)
There is growing recognition that build-to-rent (BTR), a novel institutional asset class, could improve rental affordability and housing choice in Australia. Despite favourable market conditions and increasing demand, Australia’s BTR sector remains underdeveloped compared to the US and UK. Although the asset class has attracted significant foreign institutional capital, there is little interest from domestic institutional funds. This contrasting investment behaviour between foreign and domestic funds has brought a new dimension to the debates on BTR in Australia. The study uses qualitative research design to examine institutional investor behaviour towards BTR in Australia. Interviews were conducted with experienced BTR investors across three countries—Australia, the US, and the UK—to understand the barriers and investment behaviour towards BTR. The study finds that the key barriers hindering BTR growth in Australia include unfavourable tax treatment, complex planning processes, and insufficient affordable housing incentives. Institutional investors’ decisions are influenced by firm characteristics, operational capabilities, and risk attitudes. Due to risk considerations, Australian superfunds prefer stabilised assets over new developments. Also, sustainability and ESG factors are increasingly important considerations in BTR investment decisions. The research highlights the need for a supportive regulatory environment, efficient property management, and innovative financing solutions to boost BTR investments. To accelerate BTR growth in Australia, policymakers should address tax disparities, streamline planning processes, and enhance affordable housing incentives. Developing BTR-responsive financial instruments could reduce financing costs and attract more institutional capital to the sector.